2018
DOI: 10.3389/fmicb.2018.00699
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Changes Vertical Distribution of Soil Bacterial and Fungal Communities

Abstract: Tillage can strongly affect the long-term productivity of an agricultural system by altering the composition and spatial distribution of nutrients and microbial communities. The impact of tillage methods on the vertical distribution of soil microbial communities is not well understood, and the correlation between microbial communities and soil nutrients vertical distributions is also not clear. In the present study, we investigated the effects of conventional plowing tillage (CT: moldboard plowing), reduced ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(107 citation statements)
references
References 74 publications
9
87
1
2
Order By: Relevance
“…Both the Dong et al (2017) and Sengupta and Dick (2015) study sites had silt loam soils, while soils in the current study ranged from a very fine sandy loam at one end of the field to a silty clay loam at the other, with veins of clay soil running through 12 of the 24 plots (six no till and six reduced till). Similar to the current study, Sun et al (2018) also found bacterial OTU richness was greater in conventional and rotary tillage compared to no till soil. A potential reason for this decrease in diversity could be the release of nutrients from decomposing crop residues on the soil surface, promoting the proliferation of bacterial groups involved in organic matter breakdown.…”
Section: Valuessupporting
confidence: 89%
See 2 more Smart Citations
“…Both the Dong et al (2017) and Sengupta and Dick (2015) study sites had silt loam soils, while soils in the current study ranged from a very fine sandy loam at one end of the field to a silty clay loam at the other, with veins of clay soil running through 12 of the 24 plots (six no till and six reduced till). Similar to the current study, Sun et al (2018) also found bacterial OTU richness was greater in conventional and rotary tillage compared to no till soil. A potential reason for this decrease in diversity could be the release of nutrients from decomposing crop residues on the soil surface, promoting the proliferation of bacterial groups involved in organic matter breakdown.…”
Section: Valuessupporting
confidence: 89%
“…Similar to the current study, Sun et al . () also found bacterial OTU richness was greater in conventional and rotary tillage compared to no till soil. A potential reason for this decrease in diversity could be the release of nutrients from decomposing crop residues on the soil surface, promoting the proliferation of bacterial groups involved in organic matter breakdown.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Analysis of the high-throughput sequencing data. The bioinformatic analyses were performed mainly with QIIME (Quantitative Insights Into Microbial Ecology, version 1.9.1) (58) according to the methods described in a previous study (59). In brief, the barcode sequences and adapter sequences and 55 bases of low quality at the end of the reads were discarded.…”
Section: Methodsmentioning
confidence: 99%
“…on which sustainability relies [9,10], so understanding community differences among agricultural and natural systems is critical to increase sustainability. Agricultural systems implement many cropping practices that act as abiotic and biotic filters of microbial communities [11][12][13][14]. Repeated soil disturbance, such as in a conventionally tilled agriculture system, often leads to changes in the diversity and overall community structure of soil communities [11,15].…”
Section: Introductionmentioning
confidence: 99%